A Human Dectin-2 Deficiency Associated With Invasive Aspergillosis. (18th March 2021) - Griffiths, James S; White, P Lewis; Czubala, Magdalena A; Simonazzi, Elena; Bruno, Mariolina; Thompson, Aiysha; Rizkallah, Pierre J; Gurney, Mark; da Fonseca, Diogo M; Naglik, Julian R; Ingram, Wendy; Wilson, Keith; et al.
Abstract: Immunocompromised patients are highly susceptible to invasive aspergillosis. Herein, we identified a homozygous deletion mutation (507 del C) resulting in a frameshift (N170I) and early stop codon in the fungal binding Dectin-2 receptor, in an immunocompromised patient. The mutated form of Dectin-2 was weakly expressed, did not form clusters at/near the cell surface and was functionally defective. Peripheral blood mononuclear cells from this patient were unable to mount a cytokine (tumor necrosis factor, interleukin 6) response to Aspergillus fumigatus, and this first identified Dectin-2–deficient patient died of complications of invasive aspergillosis. Abstract : We identified a Dectin-2 N170I mutation in an immunocompromised patient who died of complications of invasive aspergillosis. This mutation results in an early stop codon and poor receptor expression and renders Dectin-2 functionally defective.